The Absence of Quadrupolar Nuclei Facilitates Efficient 13C Hyperpolarization via Reversible Exchange with Parahydrogen. Issue 12 (18th May 2017) - Barskiy, Danila A.; Shchepin, Roman V.; Tanner, Christian P. N.; Colell, Johannes F. P.; Goodson, Boyd M.; Theis, Thomas; Warren, Warren S.; Chekmenev, Eduard Y.
Abstract: Nuclear spin hyperpolarization techniques are revolutionizing the field of 13 C molecular MRI. While dissolution dynamic nuclear polarization ( d ‐DNP) is currently the leading technique, it is generally slow (requiring ≈1 h) and costly (≈USD10 6 ). As a consequence of carbon's central place in biochemistry, tremendous progress using 13 C d ‐DNP bioimaging has been demonstrated to date including a number of clinical trials. Despite numerous attempts to develop alternatives to d ‐DNP, the competing methods have faced significant translational challenges. Efficient hyperpolarization of 15 N, 31 P, and other heteronuclei using signal amplification by reversible exchange (SABRE) has been reported in 2015, but extension of this technique to 13 C has proven to be challenging. Here, we present efficient hyperpolarization of 13 C nuclei using micro‐Tesla SABRE. Up to ca. 6700‐fold enhancement of nuclear spin polarization at 8.45 T is achieved within seconds, corresponding to P 13C ≈4.4 % using 50 % parahydrogen ( P 13C >14 % would be feasible using more potent ≈100 % parahydrogen). Importantly, the 13 C polarization achieved via SABRE strongly depends not only upon spin–lattice relaxation, but also upon the presence of 15 N ( I =1/2) versus quadrupolar 14 N ( I =1) spins in the site binding the hexacoordinate Ir atom of the catalytic complex. We show that different 13 C nuclei in the test molecular frameworks—pyridine and acetonitrile—can be hyperpolarized, including 13 C sites up to five chemical bonds away from the exchangeable hydrides. The presented approach is highly scalable and can be applied to a rapidly growing number of biomolecules amendable to micro‐Tesla SABRE. Abstract : Efficient hyperpolarization of 13 C nuclei using micro‐Tesla signal amplification by reversible exchange (SABRE) is reported. A significant enhancement of nuclear spin polarization at 9.4 T (up to ca. 1900‐fold) is achieved within seconds.